Antidepressant Adherence: Are Patients Taking Their Medications? - Sansone, Randy A. (Matrix Medical Communications, 2012)
Depression is a relatively common clinical disorder and can be difficult to effectively treat according to findings from the Sequenced Treatment Alternatives to Relieve Depression study. Given this working terrain, patient adherence with antidepressant therapy is a critical aspect of effective clinical management. However, according to contemporary data (i.e., over the past 10 years), approximately 50 percent of psychiatric patients and 50 percent of primary care patients prematurely discontinue antidepressant therapy (i.e., are nonadherent when assessed at sixmonths after the initiation of treatment). The reasons behind patient nonadherence to antidepressants are varied and include both patient factors (e.g., concerns about side effects, fears of addiction, belief that these medications will not really address personal problems) as well as clinician factors (e.g., lack of sufficient patient education, poor follow-up). An awareness of the high rates of antidepressant nonadherence among patients hopefully will underscore to the prescriber the importance of carefully exploring patient concerns about these medications and closely monitoring patients while on therapy.